2015
DOI: 10.5812/ijp.25(3)2015.322
|View full text |Cite
|
Sign up to set email alerts
|

Psychological Aspects in Children and Adolescents with Major Thalassemia: A Case-Control Study

Abstract: Background:Thalassemia is an inherited blood disease. It is a serious public health problem throughout the Mediterranean region, the Middle East and the Indian subcontinent, as well as in Southeast Asia.Objectives:Thalassemia is an inherited blood disease. It is a serious public health problem. In this study we assessed psychological aspects in Iranian children and adolescents with thalassemia major.Patients and Methods:In this case-control study sixty healthy subjects aged 7-18 years and Sixty Patients with c… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
2

Citation Types

2
27
3
2

Year Published

2017
2017
2023
2023

Publication Types

Select...
8

Relationship

0
8

Authors

Journals

citations
Cited by 33 publications
(34 citation statements)
references
References 28 publications
2
27
3
2
Order By: Relevance
“…According to the findings of a study in Iran, 44% of the children affected by thalassemia major had anxiety and depression and 74% had a low quality of life (14). chological issues and lower quality of life in children with thalassemia major, compared to their other counterparts (8). However, more than 90% of these children continue their lives even possibly until their fourth decade, if they receive suitable cares (15).…”
Section: Introductionmentioning
confidence: 99%
See 1 more Smart Citation
“…According to the findings of a study in Iran, 44% of the children affected by thalassemia major had anxiety and depression and 74% had a low quality of life (14). chological issues and lower quality of life in children with thalassemia major, compared to their other counterparts (8). However, more than 90% of these children continue their lives even possibly until their fourth decade, if they receive suitable cares (15).…”
Section: Introductionmentioning
confidence: 99%
“…Approximately 2 -3 million people are estimated to be carriers of beta-thalassemia and 25,000 patients exist in Iran (8). More than 2000 cases of beta-thalassemia major have been documented in Sistan and Baluchistan province (9).…”
Section: Introductionmentioning
confidence: 99%
“…Baraz, Miladinia, & Mosavinouri (2016) stated that teenagers with thalassemia do not experience the development of adulthood like a healthy teenager, this is the difference between healthy adolescents and adolescent with thalassemia. According to Behdani et al (2015), depression in teenage children with thalassemia was around 26.7%, seen as significant compared to healthy. Tab1e 1, the number of male respondents was around 42.9% and women (57.1%).…”
Section: Discussionmentioning
confidence: 99%
“…The research conducted by Shaligram et al (2007), showed that 44% of thalassemia teenagers had psychological problems, including anxiety 67%, emotional problems, especially depression, 62% and behavioral problems 49%. Another study conducted by Behdani et al (2015), regarding depression in adolescents with thalassemia, showed that patients with thalassemia experienced depression of about 26.7%, significant discharge compared to healthy children. According to Pattanashetti et al (2017), the prevalence of depression in thalassemia reached 41.94% with the majority of them had mild depression.…”
Section: Introductionmentioning
confidence: 98%
“…Our comprehensive search shows that most psychological studies that conducted on patients with thalassemia have tried to assess different aspects of their mental properties (Behdani et al, 2015;Pattanashetti, Mugali, Pattanashetty, & Patil, 2017) but there are no psychological interventional studies on their problems with the ACT method. In the process of treatment by the ACT, psychological flexibility has introduced as the basis of psychological health.…”
Section: Discussionmentioning
confidence: 99%